2000
DOI: 10.1071/wr99031
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of sodium monofluoroacetate (1080) in buried fox baits

Abstract: The degradation of 1080 in buried Foxoff® baits was investigated. Baits were exposed to 5 different treatments: shelf-stored controls, prevailing weather, no rainfall, average weekly rainfall and twice average weekly rainfall. Curvilinear regression models were used to model the rates of decay of 1080. These predicted that under normal rainfall conditions, baits would become non-lethal to working dogs at 2.2 weeks and foxes at 2.8 weeks. Management implications of these results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 19 publications
0
41
1
Order By: Relevance
“…Management of both techniques in field conditions would be similar. In Foxoff ® baits, features of cabergoline degradation are comparable to features of 1080 poison degradation (Saunders et al 2000). These include stability in dry conditions in the first 2 weeks, but the potential for rapid loss over this period through leaching and decomposition by insects, followed by breakdown of the carrier bait in the third week, and retention of low levels of the active agent for up to 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of both techniques in field conditions would be similar. In Foxoff ® baits, features of cabergoline degradation are comparable to features of 1080 poison degradation (Saunders et al 2000). These include stability in dry conditions in the first 2 weeks, but the potential for rapid loss over this period through leaching and decomposition by insects, followed by breakdown of the carrier bait in the third week, and retention of low levels of the active agent for up to 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…To progress towards registration, information is required on the stability of cabergoline in baits that are deployed under field conditions. Comparable studies have been conducted on the degradation of 1080 in baits (Fleming and Parker 1991;Saunders et al 2000). It is therefore important to determine whether cabergoline in baits, when exposed to a range of field conditions, can remain effective over a two-week baiting period and, if not recovered, for how long it would remain available to non-targets, such as pregnant domestic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that buried baits have the lowest non-target uptake compared with surface-laid baits [32,33,34], and we showed evidence that foxes were indeed interested in buried baits in this study. A fox was observed digging up a buried bait more than a month after it was placed out; if this had been a toxic (sodium fluoroacetate; “1080”) bait, it is unlikely it would still contain a lethal dose of 1080 to kill a fox due to leaching into the soil with rainfall or decay of 1080 by microorganisms [35]. Investigating different options that have increased longevity (e.g., poisoned chicken egg baits) may therefore be required.…”
Section: Discussionmentioning
confidence: 99%
“…Such degradation could ultimately result in the ingestion of sublethal amounts of bait. Several soil bacteria are capable of rapidly degrading 1080, and buried meat baits used for wild dog and fox control are known to have reduced longevity (Saunders et al 2000;Twigg et al 2000;Twigg and Socha 2001). The effectiveness of buried pig bait would also need to be tested in other regions before it became standard practice.…”
Section: Discussionmentioning
confidence: 99%